2022
DOI: 10.3390/ma15072616
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ductile and Durable High Strength Concrete (HSC) through Interactive Incorporation of Coir Waste and Silica Fume

Abstract: The issue of brittleness and low post-peak load energy associated with the plain HSC led to the development of fiber-reinforced concrete (FRC) by using discrete fiber filaments in the plain matrix. Due to the high environmental impact of industrial fibers and plasticizers, FRC development is ecologically challenged. Sustainability issues demand the application of eco-friendly development of FRC. This study is aimed at the evaluation of coir as a fiber-reinforcement material in HSC, with the incorporation of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The observed increase in chloride permeability with the addition of JF can be attributed to an increase in the permeable porosity of the concrete, which allows for faster movement of chloride ions. As previously discussed, plant-based fibres such as JF are inherently porous in nature, and their incorporation into the concrete matrix can negatively impact its imperviousness [7,48]. The addition of SF was found to be effective in reducing the RCIP value of the concrete.…”
Section: Rapid Chloride Ion Permeabilitymentioning
confidence: 71%
See 1 more Smart Citation
“…The observed increase in chloride permeability with the addition of JF can be attributed to an increase in the permeable porosity of the concrete, which allows for faster movement of chloride ions. As previously discussed, plant-based fibres such as JF are inherently porous in nature, and their incorporation into the concrete matrix can negatively impact its imperviousness [7,48]. The addition of SF was found to be effective in reducing the RCIP value of the concrete.…”
Section: Rapid Chloride Ion Permeabilitymentioning
confidence: 71%
“…Cracking in PC can occur from various causes, including tensile loads and micro-cracks resulting from plastic and/or autogenous shrinkage during pre-hardening or drying shrinkage in the hardened state [4,5]. Inherent cracks allow harmful fluids to penetrate, compromising the durability of the concrete structure by subjecting it to detrimental chemicals [6,7]. Improving the tensile performance, crack resistance, and strain-hardening response of PC is a significant area of focus in the field of concrete technology [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the reported enhancements in the flexural strength of most of the plant-fiber-reinforced cementitious composites may significantly contribute to the structural performance of pavements [277]. However, the hybrid effect of plant fibers with natural mineral fibers will be an interesting area to explore for civil engineering applications, because previous studies [278][279][280][281][282][283][284][285][286] have reported the enhanced mechanical properties of concrete with the use of natural mineral fibers.…”
Section: Flexural Strengthmentioning
confidence: 99%
“…The reinforced concrete (RC) evolution have been an ongoing process with so many advancements (Ahmad et al, 2022;Ahmed et al, 2022;Ali et al, 2022;Ashraf et al, 2022;Ghareeb et al, 2022;Huang et al, 2022;Khan et al, 2022;Li et al, 2022;Mohammed et al, 2022;Shen et al, 2022;Zou et al, 2023a;Zou et al, 2023b). High-strength concrete (HSC), especially that with fiber-RC (FRC) is a versatile form of a concrete mixture with superior performance compared to that of normal RC without fiber reinforcement (Deifalla, 2021a;Deifalla et al, 2021).…”
Section: Introductionmentioning
confidence: 99%